The difficult construction of a European Deposit Insurance Scheme: a step too far in Banking Union?. Issue 3 (3rd July 2018) - Howarth, David; Quaglia, Lucia
Abstract : The German Government refused to accept the development of a European Deposit Insurance Scheme (EDIS) for Banking Union member states. Publicly,  the German Government was preoccupied with the creation of a moral hazard that common funds would create for banks in those participating countries that had weak banking systems. This paper argues that to understand German moral hazard concerns it is necessary to look beyond the ideational – notably concerns stemming from German Ordo-liberalism – and focus on the existing national institutional arrangements that the German Government sought to protect. German moral hazard concerns stemmed from the fear that well-funded German deposit guarantee schemes (DGS) – especially those of small savings and cooperative banks – could be tapped to compensate for underfunded (and largely ex post funded) DGS in other member states. We thus demonstrate that the difficulties facing the construction of an EDIS owe to the weakness of the previously agreed harmonization of national DGS. This failure to harmonize schemes beyond a low minimal standard can be explained through an analysis focused on national systems. Different existing national DGS stem from the different configuration of national banking systems, the longstanding relationships among national banks and well-entrenched regulatory frameworks.